Event‐based precipitation characteristics related to cloud‐top temperature during pre‐summer rainy season over south China. (4th January 2023) - Zhang, Aoqi; Chen, Yilun; Li, Weibiao; Chen, Shumin
Abstract: Precipitation exists in the form of event, which means all pixels within the same event have similar atmospheric condition and development experiences. Therefore, using GPM DPR and Himawari‐8 AHI data from 2016 to 2020, we carried out event‐based investigations on precipitations during the pre‐summer rainy season over south China. The identified rain clusters (RCs) were classified into three classes based on the mode of cloud‐top temperature, including those <230, 230–265, and >265 K. The results show that RCs with mode of cloud‐top temperature <230 K were related to low‐level velocity and jet. The atmospheric layer was very unstable with sufficient moisture supply, so the ratio of convective precipitation reached as high as 20% with largest droplet size. RCs at 230–265 K were mainly frontal stratiform precipitations caused by quasi‐stationary front. The atmospheric layer was stable but the horizontal moisture flux was strong; precipitations often appeared as continuous light rain with high droplet density and small droplet size. RCs with mode of cloud‐top temperature >265 K contributed less than 10% of the accumulated rainfall amount. They were mainly warm‐cloud shallow precipitations triggered by local convection with low droplet density. Our results suggest that the event‐scale characteristics of precipitation are indicative of the triggers and microphysics of precipitation. Abstract : Taxonomy researches of precipitations were conducted based on the event‐scale features of cloud‐top temperature during pre‐summer rainy season over south China. Rain clusters with variant mode of cloud‐top temperature had significantly different properties of triggering mechanism, horizontal distribution, vertical structure, and microphysics.